Towards a Visual SPARQL-DL Query Builder - Giménez, Christian (2018)
Querying ontologies is an every-day activity that users need. This interaction will improve when the query is more expressive and easier to develop. For this purpose, a visual query language is an ideal mean for users and ontology engineers for creating queries taking advantage of the easy-to-understand and low time and cost characteristics, specially, for users which does not know textual query languages. On the other side, SPARQL-DL is a powerful and expressive textual query language for OWL-DL based ontologies that can combine TBox/ABox/RBox queries. Considering the advantage of both, we present in this work a visual query language that can be interpreted as SPARQL-DL sentences and thus being used for querying ontologies for its structure and/or instance information. Altogether, we use this idea to create a modified version of crowd, a Web modelling tool with reasoning support, that enables to implement and tests the presented graphical language along with the needed SPARQL-DL support for solving queries with the user’s provided OWL 2 ontologies in any of its linearisations.